Scaffolding Humor Comprehension Through Pause-and-Discuss in Indonesian EFL Classrooms - Pratama, Hendi (Elsya : Journal of English Language Studies, 2025)
This study aims to explore the effectiveness of a pause-and-discuss approach in integrating stand-up comedy into English as a Foreign Language (EFL) instruction. This qualitative case study utilized twenty-six undergraduates from an English class at an Indonesian university. Data comprised a Likert-scale survey, open-ended written reflections, and classroom discussions. Survey responses were summarized using descriptive statistics, and the qualitative data were thematically coded based on Saldana’s (2016), with  triangulation across sources. Results indicate that while learners initially experienced difficulties in processing humor due to idiomatic language, rapid delivery, and cultural references, the pause-and-discuss strategy enabled them to scaffold comprehension collaboratively, improve vocabulary retention, and enhance pragmatic awareness. Exposure to authentic stand-up performances developed learners’ intercultural competence, allowing them to compare cultural perspectives and negotiate meaning beyond textbook learning. While previous studies on humor pedagogy in EFL context have provided descriptive account without cross-source validation, this research fills that gap through a triangulated design validating the pedagogy, whereas existing studies offer descriptive accounts without cross-source checks. Broader implications suggest that humor can be deliberately integrated into curriculum design and that teacher training programs should include preparation for scaffolding humor in EFL contexts, making classrooms more engaging, culturally responsive, and learner-centered.